Distinct Neuropsychological Correlates of Cognitive, Behavioral, and Affective Apathy Sub-Domains in Acquired Brain Injury - Njomboro, Progress; Deb, Shoumitro (Frontiers in Neurology, 2014)
Apathy has a high prevalence and a significant contribution to treatment and rehabilitation outcomes in acquired brain damage. Research on the disorder’s neuropsychological correlates has produced mixed results. While the mixed picture may be due to the use of varied assessment tools on different patient populations, it’s also the case that most studies treat apathy as a unitary syndrome. This is in spite of evidence that apathy is a multifaceted and multidimensional syndrome. This study investigates the neuropsychological correlates of apathy in 49 patients with acquired brain damage. It further fractionates apathy symptoms into affective, cognitive and behavioural sub-domains, and investigates their individual relations with standard measures of affective, cognitive and behavioural functioning. Global apathy scores were not related to any of these measures. Affective apathy was associated with emotion perception deficits, and cognitive apathy was associated with executive deficits on the Brixton test. These results demonstrate that treating apathy as a single entity may hide important correlates to apathy symptoms that become visible when the disorder is fractionated into its sub-domains. The study highlights the research and clinical importance of treating apathy as a multidimensional syndrome.